2015
DOI: 10.1161/atvbaha.115.306048
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD25 + Innate Lymphoid Cells Reduces Atherosclerosis

Abstract: Objective Innate lymphoid cells (ILCs) are a newly discovered subset of immune cells that promote tissue homeostasis and protect against pathogens. ILCs produce cytokines also produced by T lymphocytes that have been shown to affect atherosclerosis, but the influence of ILCs on atherosclerosis has not been explored. Approach and Results We demonstrate that CD25+ ILCs that produce type 2 cytokines (ILC2s) are present in the aorta of atherosclerotic immunodeficient ldlr−/−rag1−/− mice. To investigate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 28 publications
2
44
1
1
Order By: Relevance
“…3B). However, as reported in previous work26, IL-2 treatment was not without a number of off-target effects, the most common of which was an increase in splenic fibrosis in the IL-2 treated group, which was severe in some mice (Supplementary Fig. 3C).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…3B). However, as reported in previous work26, IL-2 treatment was not without a number of off-target effects, the most common of which was an increase in splenic fibrosis in the IL-2 treated group, which was severe in some mice (Supplementary Fig. 3C).…”
Section: Resultssupporting
confidence: 71%
“…Previous studies suggested a potential role for ILC2 in the modulation of atherosclerosis2326. However, those studies used immune-compromised animals and relied on non-physiological exogenous and chronic administration of cytokines (that is, IL-2 and IL-25) that are not specific for the ILC2 population, and that can promote ILC2-independent immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of atherosclerotic lesion size was performed on 5 Oil-Red-O stained cryosections (10 μm each) spanning 160 μm of the three valve area of the aortic root, as described (28, 29). …”
Section: Methodsmentioning
confidence: 99%
“…One ‘side effect’ of this strategy is that IL‐2 may also expand CD25 + innate lymphoid cells. The role of these cells in atherosclerosis is just beginning to be investigated (Engelbertsen et al, ). Furthermore, there is incomplete knowledge on how IL‐2 therapy affects the emerging plasticity of Tregs (Butcher et al, ).…”
Section: Therapeutic Strategies Targeting the Adaptive Immune Systemmentioning
confidence: 99%